Grateful Cooperation: Cistercian Inspiration for Ecosystem Ethics - Schaefer, Jame (Cistercian studies quarterly, 2002)
Focuses on the efforts of contemporary philosophers to reflect on the human relation to ecological systems. Depiction of the ongoing cooperation among the monks, animal and plant species; Functions of humans in relation to others species and inanimate constituents; Emphasis on human-in-ecosystem philosophy.